(3QSGdg aj GdJhMjOs - (3CHi eMeO YHO Gddg Hf CHi RjO YHO GdQMef GdfaQj GdbjQhGfis
(3ChdgG (B:s
(3GdeSFdI GdKGfjI hGdYTQhf CeG HYO eeG PcQg GdeTQchf Yfi Cfi Cfgi Ydi GdUdGI Ydi GdfHi Udi Gddg Ydjg hSde hHgJGf CaJQGg Ydi GdTjGWjf s
(3BNQgG (B:s
(3hgh YHGOg GdCUfGe ef aYdg caQ hJHQA efg QShd Gddg Udi Ydjg hSde jG YHGO Gddg JacQ hJPcQhG hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(404 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds